Microbial-Based Double-Stranded RNA Production to Develop Cost-Effective RNA Interference Application for Insect Pest Management. (April 2019) - Ahn, Seung-Joon; Donahue, Kelly; Koh, Youngho; Martin, Robert R.; Choi, Man-Yeon
RNA interference (RNAi) is a convenient tool to identify and characterize biological functions in organisms. Recently, it has become an alternative to chemical insecticides as a biologically based control agent. This promising technology has the potential to avoid many problems associated with conventional chemical insecticides. In order for RNAi application to be practical for field use, a major hurdle is the development of a cost-effective system of double-stranded RNA (dsRNA) production for a large quantity of dsRNA. A handful of research reports has demonstrated microbial-based dsRNA production using L4440 vector and HT115 (DE3) Escherichia coli for application to vertebrate and invertebrate systems. However, the dsRNA yield, production efficiency, and biological purity from this in vitro system is still unclear. Thus, our study detailed biochemical and molecular tools for large-scale dsRNA production using the microbial system and investigated the production efficiency and yield of crude and purified dsRNAs. An unrelated insect gene, green fluorescent protein (GFP), and an insect neuropeptide gene, pyrokinin (PK) identified from Drosophila suzukii, were used to construct the recombinant L4440 to be expressed in the HT115 (DE3) cell. A considerable amount of dsRNA, 19.5 µg/mL of liquid culture, was isolated using ultrasonic disruption followed by phenol extraction. The sonication method was further evaluated to extract crude dsRNA without the additional phenol extraction and nuclease treatments and also to reduce potential bacterial viability. The results suggest that the ultrasonic method saved time and costs to isolate crude dsRNA directly from large volumes of cell culture without E coli contamination. We investigated whether the injection of PK dsRNA into flies resulted in increased adult mortality, but it was not statistically significant at 95% confidence level. In this study, the microbial-based dsRNA production has potential for applied RNAi technology to complement current insect pest management practices.